A critical discourse analysis of legitimacy, stakeholder voices, and calls to action in Saudi environmental associations - Almotiry, Omar Nooh; Wani, Neelofar Hussain (Research Journal in Advanced Humanities, 2026)
This article examines how Saudi environmental associations construct legitimacy, represent stakeholder voices, and formulate calls to action in their public discourse. Positioned at the intersection of Critical Discourse Analysis, environmental communication, nonprofit communication, stakeholder theory, and ecolinguistics, the study asks how association discourse authorizes environmental action and how it converts public concern into civic participation. The article uses a qualitative CDA design with a bounded illustrative corpus of official public-facing texts from Saudi environmental associations and association-type civic/scientific bodies, including mission statements, activity descriptions, campaign language, membership or registration prompts, and partnership-oriented webpages. The analysis develops a three-dimensional framework: legitimacy construction, stakeholder voice, and calls to action. The findings suggest that legitimacy is commonly built through national alignment, institutional affiliation, expertise, public benefit, and moral responsibility. Stakeholder voices are visible through references to citizens, volunteers, youth, communities, partners, and public/private actors, but these voices are often represented by the association rather than quoted directly. Calls to action move between operational invitations, such as registration and volunteering, and broader moral appeals to protect the environment. The article contributes a humanized, replicable CDA framework for analyzing how environmental associations use language to build trust, organize participation, and shape civic environmental responsibility, while cautioning against claims of actual environmental impact without independent evidence.